The Expectation-Based Loss-Averse Newsvendor - Fabian Herweg (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
We modify the classic single-period inventory management problem by assuming that the newsvendor is expectation-based loss averse according to Köszegi and Rabin (2006, 2007). Expectation-based loss aversion leads to an endogenous psychological cost of leftovers as well as stockouts. If there are no monetary stockout costs, then the loss-averse newsvendor orders a quantity lower than the quantity ordered by a profit-maximizing newsvendor. If there are positive monetary costs associated with stockouts, then the loss-averse newsvendor places suboptimal orders, which can be either too high or too low.
urn:nbn:de:bvb:19-epub-14061-3
Keywords: 330; behavioral; Lagerhaltungsmodell; Risikoaversion; Erwartungstheorie; Verhaltensökonomik; Theorie